Harvesting microalgae with microwave synthesized magnetic microparticles - Prochazkova, Gita; Safarik, Ivo; Branyik, Tomas (Bioresource technology, 2013)
To make magnetic harvesting a more viable option, a suspension of inexpensive iron oxide magnetic microparticles (IOMMs) prepared by microwave treatment is presented as a new agent for separating Chlorella vulgaris from a highly diluted suspension. Separation efficiencies were tested under various conditions (model environment, cultivation media, different pH), revealing not only a dependency on the pH and amount of IOMMs, but also the influence of the ions present in the culture medium. Phosphorus ions were identified as the medium component interfering with algae-IOMMs interactions that are essential for magnetic cell separations in the culture medium. Phosphorus limited C. vulgaris cells were magnetically separated from the medium at separation efficiencies of over 95% at a 3:1 mass ratio of IOMMs to microalgae. A rapid and complete demagnetization of harvested algae was achieved by acidic treatment (10vol.% H(2)SO(4)) at 40°C under the influence of ultrasound.
Keywords: Microalgae; biomasa; magnetické nanočástice; Culture Media; mikrořasy; studie proveditelnosti; Magnetite Nanoparticles; Chlorella vulgaris; kultivační média; Biomass; Feasibility Studies